SLIM 2006 - Shelf-life International Meeting - Special issue of "Italian Journal of Food Science" - Mancusi, Chiara (Italian Journal of Food Science, 2019)
This Special Issue of the Italian Journal of Food Science collects the presentations given at the “SLIM 2006, Shelf-life International” congress organised by GSICA, Department DOFATA, University of Catania, held at Catania on 21-23 June 2006.These papers were reviewed by the Scientific Committee of the congress before their presentation but they did not undergo the conventional reviewing system of the Italian Journal of Food Science.